Laboratory stand for car tire diagnostics - N. V. Holshev; D. N. Konovalov; A. V. Prokhorov; P. S. Minaev (Вестник СибАДИ, 2022)
Introduction. An automobile vehicle consists of a large number of parts that affect traffic safety in different ways. The elements that critically affect the safety of the vehicle include automobile pneumatic tires. Their technical condition is currently being assessed visually, without the use of special equipment. This diagnostic method does not provide detection of hidden tire damage. This article describes the proposed method of diagnosing pneumatic tires of passenger cars, as well as the scheme of the stand for its implementation.Materials and methods. Based on previous studies, it was proposed to use the static stiffness of automobile tires as a diagnostic parameter when assessing their technical condition. To implement the use of this diagnostic parameter, a new method for assessing the technical condition of tires was proposed. It consists in determining and comparing the values of the static stiffness of the tire at its various points with the average stiffness value at all measurement points. To implement this method in the laboratory, a schematic diagram of the stand was proposed.Results. In accordance with the proposed scheme of the stand, a volumetric model of the stand was developed for the implementation of the proposed method in laboratory conditions, and the frame of the stand was made and its main elements were selected. As a converter of the rotational movements of the potentiometer handle into the electronic signal, it was decided to use the Arduino Uno R3 analog-to-digital converter. Software was also developed to automate the reading and processing of bus diagnostic results.Discussion and conclusions. The proposed method of tire diagnostics and the stand implementing it can increase the efficiency and simplicity of assessing the technical condition of pneumatic tires of passenger cars. Further research is needed to assess the effectiveness of the proposed solutions.